(untitled) (Revista Latino-Americana de Enfermagem, 2019)
Purpose: to describe the meanings that patients attribute to the term cancer survivor and to analyze the identities assumed by them according to their experience with the disease. Methods: qualitative study with a narrative method, theoretical framework of the medical anthropology and identity concept. The study included 14 participants, men and women, diagnosed with urologic cancer. The semi-structured interviews were performed at the individual’s home, after confirming participation. Results: eight participants assumed to be survivors, but five also assumed at least one other identity, in addition to cancer survivor. In contrast, among the six who defined themselves as cured, only one indicated another identity. Four considered themselves as victims and only two as cancer patients. However, the latter – cancer patient and victim – assumed at least one other associated identity. Conclusions: allowing patients to reflect on themselves and their experience with the disease, as well as attributing themselves a new identity, will be directly related to the wellbeing and momentum the survivor is going through. Therefore, it can direct care in the cancer survivorship phase according to each survivor’s individual context.